When multiple primary lung cancers express the same rare mutation: a case report - Han, Yaqing; Geng, Yandong; Sui, Qian; Liu, Yanjie; Xie, Shaonan; Gao, Maogang; Liu, Qingyi; Liu, Guangjie; Wang, Shize (Frontiers in Oncology, 2024)
The debate continues whether the expression of the same rare genetic mutation in multiple primary lung cancers suggests intrapulmonary metastasis or truly multiple primary lung cancers. We report a case of a 54-year-old female patient who presented with multiple nodules in the right lung discovered during a routine examination, persisting for six months. The patient had three central lesions in the right lung’s upper, middle, and lower lobes. She underwent thoracoscopic wedge resection, and the postoperative pathology reported two minimally invasive adenocarcinoma and one adenocarcinoma in situ. Interestingly, genetic testing for lung cancer-related driver genes revealed the presence of the rare RET mutation in all three nodules. This led us to speculate that these nodules might have the exact origin rather than being multiple primaries. To verify this hypothesis, we conducted further testing on these nodules, including whole-exome sequencing (The NGS data was generated from the Illumina sequencing platform by Novogene Co. Ltd, Beijing, China). The results indicated that although all three nodules expressed the RET mutation, there was significant heterogeneity in the gene mutations (differences in the number of cellular mutations, substitution composition levels, and clustering analysis of the three nodules). Thus, the patient was considered to have multiple primary lung cancers. In such cases, whole-exome sequencing can distinguish whether the nodules have the exact origin.